2013
DOI: 10.1007/s12011-013-9672-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Magnesium Supplementation Improve Body Composition and Muscle Strength in Middle-Aged Overweight Women? A Double-Blind, Placebo-Controlled, Randomized Clinical Trial

Abstract: Muscle strength, an independent predictor of metabolic disorders, disability, and mortality, reduces gradually with advancing age. Little is known about the influence of nutritional intervention on muscle strength in middle-aged. The aim of the present study is to examine whether magnesium could improve body composition and muscle strength in middle-aged overweight women. In this double-blinded, placebo-controlled, randomized trial, a total of 74 healthy middle-aged overweight women (25 ≤ BMI ≤ 30 kg/m(2)) rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 38 publications
4
27
3
Order By: Relevance
“…In the results of the sensitivity analysis, to determine whether the weight loss associated with chronic disease conditions would impact on the main results, we found no differences in the associations compared with our main findings (data not shown). The positive associations we found between grip strength and Mg in men and women in our study contrast with the two other cross-sectional studies and one intervention study that found no association with grip strength, despite one recent intervention study finding a significant effect of supplemental Mg on certain functional measures which were more pronounced in women with low intakes of Mg [20,29,30,40]. Another study found a positive association between serum Mg and hand grip strength [27] but serum Mg does not reflect dietary intake well partly due to the tight homeostasis in blood, which is mediated by the reservoir of Mg within bone.…”
Section: Sensitivity Analysiscontrasting
confidence: 99%
See 2 more Smart Citations
“…In the results of the sensitivity analysis, to determine whether the weight loss associated with chronic disease conditions would impact on the main results, we found no differences in the associations compared with our main findings (data not shown). The positive associations we found between grip strength and Mg in men and women in our study contrast with the two other cross-sectional studies and one intervention study that found no association with grip strength, despite one recent intervention study finding a significant effect of supplemental Mg on certain functional measures which were more pronounced in women with low intakes of Mg [20,29,30,40]. Another study found a positive association between serum Mg and hand grip strength [27] but serum Mg does not reflect dietary intake well partly due to the tight homeostasis in blood, which is mediated by the reservoir of Mg within bone.…”
Section: Sensitivity Analysiscontrasting
confidence: 99%
“…Few studies have investigated sarcopenic risk factors with dietary magnesium in middle and older aged populations and even fewer investigated these associations according to gender. Grip strength has been investigated only in 5 previous studies with dietary or supplemental Mg intake or blood concentrations, and only one of these was in men [20,21,27,29,30]. Even fewer studies have investigated the associations between Mg and skeletal muscle mass, with none investigating associations in men only [20,21,29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One direct indicator of exercise performance is muscle strength. A few cross-sectional surveys [ 15 , 16 , 17 ] and randomized control trials (RCTs) [ 23 , 36 , 41 ] reported a positive association of serum Mg levels/Mg supplementation with muscle strength, but other studies indicated no significant effect [ 42 , 43 ] ( Table 3 ). A cross-sectional analysis using data from the InCHIANTI (aging in the Chianti area) study [ 15 ] found that serum Mg concentrations were positively associated with grip strength, lower-leg power, knee extension torque, and ankle extension strength in the elderly after adjustment for potential confounders such as age, body mass index and physical activity levels [ 15 ].…”
Section: The Association Between Mg and Exercise Performancementioning
confidence: 99%
“…11 Further, there is evidence linking Mg 2+ intake to body weight regulation, with low intake potentially impairing lean body mass growth, 12,13 whereas Mg 2+ supplementation may increase lean body mass and decrease fat mass in overweight women. 14 Plasma Mg 2+ levels are closely regulated and remain constant throughout life, despite the fact that dietary Mg 2+ intake and intestinal absorption decrease with age. 15 The control of Mg 2+ balance is ensured by a tightly regulated reabsorption of Mg 2+ in the distal tubular segments of the kidney.…”
mentioning
confidence: 99%